UN discussion on political situation in Oman (1960)
Letters sent to Harold Beeley on the Treaty of Sib and tactics at the UN, with regard to representations to European, Latin American and certain Arab posts. The text of the Treaty is attached, with discussions on its significance to the debate, alongside reports on the countries for and against inscription of Oman on the UN Agenda (86) Role played by the Sudanese delegation (87) Recommendation for lobbying in certain Afro-Asian countries and the suggestion that representations to Arab countries in Africa would be useless. It also includes telegrams to Arab capitals on points to raise with their respective governments (88) Suggestions on representations to various governments. It also includes a suggestion to thank the French for their support against inscription (91) Talk with Hermann Eilts about American desire to abstain on a moderate resolution due to worries around the renewal of the Dhahran base agreement with Saudi Arabia. It also includes a discussion about Iraqi arms deliveries to Saudi Arabia for Omani rebels (92) Confirmaton that the text of the Treaty of Sib published in The New York Times came from an Arab source (93) Guidance to Commonwealth Relations Office (CRO) on representations to their governments (94) J F Walker’s approach to the Norwegians and the correction of historical inaccuracies in previous communication (95) Request for information on Muscat and Oman for the Nigerian Government (96) Postponement of representations to the Sudanese government until early January 1961 (97) The Lebanese Government’s awareness of HMG’s disappointment in their actions on inscription at the UN, with no opportunity to raise the matter further at present (98) Comments from Baghdad Radio on action at the UN (99) Representations to Libya (100) Attitude of HMG to Algeria and its possible effect on Libyan attitudes towards Oman (101) Representations to Jordan (102) Decision not to ask France to lobby French Africans (103) Estimate on the voting on the Oman item at the UN (104)
Keywords: Vie politique -- Oman -- 1932-1970